The role of errorful and errorless training on error detection and learning of tracking task - Ehsan Zareıan; Karen Baranı; Majid Arab; Mehdi Dastfal (Türk Spor ve Egzersiz Dergisi)
The aim of this study is to investigate errorful and errorless training methods on detecting error in tracking task. 24 students of Allameh Tabataba'i University (Age = 23± 2.8 yrs.) were randomly selected to perform a computerized tracking test. The participants underwent a pre-test after being given verbal instructions and were divided into two groups of errorful and errorless training according to the test results. The errorless training group, during task performance, saw the target path and the path they were tracking as a diagram and detected errors according to the difference between the two paths. But the errorful training group attained the task goal by trial-and-error. Each group underwent 30 tests in 3 seperate sessions with a recovery period of 24 h in-between. The results showed the significant effect of errorful and errorless training on the progress of detecting errors in acquisition and retention stages of tracking task. Furthermore, a significant difference has been identified between the effects of errorful and errorless training methods on the acquisition and retention of tracking task. This difference was in favor of the errorless training group and this group's progress in detecting errors was more than the errorful training group. The results showed that in addition to the influence of errorful and errorless training methods on detecting error in tracking task, there is a difference between the effect of these methods in detecting error and the errorless training method has a more positive effect on participants' error detecting ability in the tracking task.